2020
DOI: 10.17705/1thci.12202
|View full text |Cite
|
Sign up to set email alerts
|

Improving Agility Using Big Data Analytics: The Role of Democratization Culture

Abstract: Background: Big data analytics (BDA) is considered an enabler of organizational agility because it helps firms to sense market-based changes and improve decision making in a more informed and timely manner. However, in reality, only a handful of firms have achieved improvement in their outcomes by using BDA. To address this inconsistency, our study explores the conditions under which BDA use translates into agility. We particularly focus on organizational culture because in the pursuit of agility, culture is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…These findings are consistent with the prior literature that have also demonstrated that the business gains can only be derived from the meaningful use of technologies, rather than the technologies themselves (Barratt & Oke, 2007;Chen et al, 2015;Dubey et al, 2019;Ghasemaghaei et al, 2017;Srinivasan & Swink, 2018). Ghasemaghaei et al (2017) and Ashrafi et al (2019) found that information technology capabilities (big data and business analytics) only have an indirect effect on agility which is consistent with findings of this study, Rialti et al (2019) and Hyun et al (2020) found that big data analytics are directly and positively related to agility. In addition, entrepreneurial orientation plays a fundamental role in the relationship between big data analytics capabilities and organizational agility.…”
Section: Discussion Implications For Theory and Practicesupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with the prior literature that have also demonstrated that the business gains can only be derived from the meaningful use of technologies, rather than the technologies themselves (Barratt & Oke, 2007;Chen et al, 2015;Dubey et al, 2019;Ghasemaghaei et al, 2017;Srinivasan & Swink, 2018). Ghasemaghaei et al (2017) and Ashrafi et al (2019) found that information technology capabilities (big data and business analytics) only have an indirect effect on agility which is consistent with findings of this study, Rialti et al (2019) and Hyun et al (2020) found that big data analytics are directly and positively related to agility. In addition, entrepreneurial orientation plays a fundamental role in the relationship between big data analytics capabilities and organizational agility.…”
Section: Discussion Implications For Theory and Practicesupporting
confidence: 92%
“…While agility has been considered a major enabler of a business’s performance and an antecedent of business value (Côrte-Real et al, 2017; Overby et al, 2006), the IT capability literature have not investigated how agility can be enhanced (Oh & Pinsonneault, 2007) and only emphasized firm performance (e.g., Ferraris et al, 2019; Mikalef et al, 2020; Rialti et al, 2019; Wamba et al, 2017). Although a limited number of studies (Ghasemaghaei et al, 2017; Hyun et al, 2020) have addressed the conditions (i.e., organizational culture and fit perspectives) under which big data can lead to agility by investigating possible moderators, the understanding of the mediator that enable big data to enhance agility is still unclear. Thus, to help us understand the mechanism that makes this relationship possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022; Chatfield and Reddick, 2018), learning culture—shared assumptions that position a firm to perceive market changes and learn from experience (Cetindamar et al. , 2021), and democratization culture—the willingness to share information and acceptance of diversity (Hyun et al. , 2020; Wang and Ali, 2021); (5) organizational fit involves the fit between information management (IM) system and the organization (Rialti et al.…”
Section: The State Of Bda-enabled Agility Researchmentioning
confidence: 99%
“…Agile SCs respond to changes quickly and recover fast, smoothly, and efficiently to the turbulences in supply and demand (Lohmer et al, 2020 ; Stone & Rahimifard, 2018 ; Wiedmer et al, 2021 ). Agility and flexibility are considered SC's reactive and responsive abilities (Hyun et al, 2020 ); though tightly twined, these are two different aspects of the SC.…”
Section: Theoretical Backgroundmentioning
confidence: 99%